2013
DOI: 10.1007/s11419-012-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid chemiluminescence assay for on-site analysis of paraquat using a portable luminometer

Abstract: Paraquat (N,N´-dimethyl-4,4´-bipyridinium dichloride) is one of the most widely used herbicides owing to its high efficacy and low environmental persistence. However, since paraquat has significant acute toxicity, fatalities are often caused by accidental or voluntary ingestion of paraquat. In consideration of the strong toxicity and fast-acting property of paraquat, on-site analysis in accident scenes should be effective for the immediate medical treatment.In this study, a simple and rapid chemiluminescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…SPE C18 cartridges have been widely used in studies [22, 23, 26, 27, 31, 34, 35]. In addition to the C18 cartridges, other cartridges such as Bond Elut® LRC-CBA, Omix SCX, and Waters Oasis WCX has used by other studies [1, 3, 29]. Baeck et al compared SPE with five extraction solvents for the LLE in postmortem blood samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…SPE C18 cartridges have been widely used in studies [22, 23, 26, 27, 31, 34, 35]. In addition to the C18 cartridges, other cartridges such as Bond Elut® LRC-CBA, Omix SCX, and Waters Oasis WCX has used by other studies [1, 3, 29]. Baeck et al compared SPE with five extraction solvents for the LLE in postmortem blood samples.…”
Section: Resultsmentioning
confidence: 99%
“…This assay was performed on the beverage with good sensitivity and accuracy. Still, it is unclear whether it has such sensitivity and accuracy on biological samples, especially postmortem samples [1]. Koivunen et al designed an assay base on Enzyme-Linked Immunosorbent Assay (ELISA) for PQ in the urine sample.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] In consequence, it is urgently desirable to develop a simple and rapid sensor for analyzing MV 2+ on-site with high selectivity and sensitivity to get sufficient information for immediate medical treatment before transporting to hospital. Several techniques for analyzing MV 2+ have been employed, including electrochemistry, [5][6][7] surfaceenhanced Raman scattering, [4] chemiluminescence, [8] colorimetric and fluorescent dual detection technique [9] and photoelectrochemistry, [10] UV-vis, [11] etc. Ribeiro et al [5] reported an electroanalytical method utilizing DNA modified gold nanoparticles immobilized on a gold electrode to detect MV 2+ .…”
Section: Introductionmentioning
confidence: 99%